The Newest Telecommunications Operator Company in Indonesia: “A Research Case Study of Smart Telecom’s Survival in the Competitive Industry” - Roy Poan (International Journal of Family Business Practices, 2021)
This paper is based on field research into the evolution of the telecommunications industry in Indonesia for the newest telecommunications operator company in Indonesia, PT Smart Telecom (ST), from the preparation of its launch to becoming one of the surviving telecommunications companies in Indonesia. The paper aim to describe the marketing, operational and the role ST plays in the Sinarmas group. Through a personal experience, the case focuses on every stage of PT Smart Telecom’s evolution until its merger with PT Mobile-8 before becoming one of the five remaining telecommunication operators in Indonesia.